STABILIZATION POND FOR WASTEWATER TREATMENT - Mohammed Ali I. Al-Hashimi; Hayder Talee Hussain (European Scientific Journal, ESJ, 2013)
This research is concerned with study and check the suitability of waste stabilization ponds (WSPs) for treating wastewater in Al-Dewaniyah province by taking a sample of community of 10000 population.Experimental work had three cases depending on many considerations such as economical and specification of final effluent. A model of two ponds (facultative and aerobic) in series was used as first case of experimental work. Then third pond with aeration process to aerobic pond were added to the series as second case to improve the effluent. At last, sand filter was used to polish the final effluent from aerobic pond.The three ponds had the same surface area (5.75m*2m) but with different depths, where it was 2m for anaerobic pond, 1.5m for facultative pond and 0.75m for aerobic pond. From the tests taken for the three cases, the results obtained for the last two cases were much better when compared with first case. Sand filter contributed in improving final effluent by decreasing total suspended solid (TSS) also in increasing removal efficiency of biochemical oxygen demand (BOD) and chemical oxygen demand (COD). At the end, the results of this work could be an invitation to use waste stabilization pond for wastewater treatment in rural areas or even small communities but it may need more examinations to get best results.